Health-Related Quality of Life of HIV Infected Persons on Antiretroviral Therapy in Jos, Plateau State Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) remains an important global health problem. People living with HIV (PLHIV) experienced physical, social and mental health challenges that can affect their quality of life (QOL).Aim:To determine the health-related quality of life (HRQOL) of HIV-infected adults.Settings and design:This was a cross-sectional study conducted in the APIN centre. One hundred and seventy-eight PLHIV were selected by a multistage sampling technique between 10 January 2018 and 31 March 2018.Materials and Methods:The world Health Organization QOL-HIV Bref Questionnaire was used to collect the information.Statistical analysis used:Data were analysed using SPSS version 23.0 statistical software We determined significant factors using Chi square and logistic regression at a 5% level of significance.Results:The physical domain has the lowest mean score of 13.25 ± 2.25, while the spiritual/religion/personal belief domain had the highest mean score of 14.955 ± 3.336. Clustered of differentiation 4 (CD4) count, adherence and currently ill status were significantly associated with QOL. The odds for good QOL were 13 times higher among those with CD4 count ≥500 cells/mm3 compared to those with CD4 count < 500 cells/mm3 (adjusted odds ratio [aOR]: 13.03; 95% confidence interval [CI]: 4.58-37.5). The odds for good HRQOL were six times higher among those with good adherence compared to those with poor adherence (aOR: 5.62;95%CI: 1.83-17.26).Conclusion:The study revealed that the spiritual/religion/personal belief domain has the highest QOL score, while the physical domain had the least score. Adherence, currently ill and CD4 count were predictors of good QOL.